2017
DOI: 10.1080/09553002.2018.1416204
|View full text |Cite
|
Sign up to set email alerts
|

Radioprotective and radiomitigative effects of BP-C2, a novel lignin-derived polyphenolic composition with ammonium molybdate, in two mouse strains exposed to total body irradiation

Abstract: BP-C2 mitigates radiation-induced damage in mid-lethal range of radiation doses. Effects are mediated by enhancement of extramedullar hematopoiesis in the spleen and a protective effect on the intestinal epithelium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…A novel lignin-derived polyphenolic composition with ammonium molybdate, BP-C2 mitigates radiation-induced damage in midlethal range of radiation doses. Effects are mediated by the enhancement of extramedullar hematopoiesis in the spleen and a protective effect on the intestinal epithelium [ 54 ]. Tea polyphenols, particularly in the combination in TP50 as the radioprotector in mice, have antioxidant potential activity and can reduce inflammatory cytokines especially during the recovery of the hematopoietic system [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…A novel lignin-derived polyphenolic composition with ammonium molybdate, BP-C2 mitigates radiation-induced damage in midlethal range of radiation doses. Effects are mediated by the enhancement of extramedullar hematopoiesis in the spleen and a protective effect on the intestinal epithelium [ 54 ]. Tea polyphenols, particularly in the combination in TP50 as the radioprotector in mice, have antioxidant potential activity and can reduce inflammatory cytokines especially during the recovery of the hematopoietic system [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hematopoietic stresses are well known to mobilize hematopoietic stem cells from the bone marrow to the spleen, which induces extramedullary hematopoiesis [16]. Bykov et al also reported that lignin-derived polyphenolic composition with ammonium molybdate improved the 30-day survival rate and increased the formation of endogenous splenic colony-forming units, indicating that the radio-mitigative effects are mediated by the enhancement of extramedullary hematopoiesis in the spleen [29]. It is therefore possible that the administration of combination #4 also enhanced the hematopoietic function in the spleen instead of the damaged bone marrow of mice exposed to lethal TBI.…”
Section: Discussionmentioning
confidence: 99%
“…Hematopoietic stresses are well known to mobilize hematopoietic stem cells from the bone marrow to the spleen, which induces extramedullary hematopoiesis [ 19 ]. Bykov et al also reported that lignin-derived polyphenolic composition with ammonium molybdate improved the 30-day survival rate and increased the formation of endogenous splenic colony-forming units, indicating that the radio-mitigative effects are mediated by the enhancement of extramedullary hematopoiesis in the spleen [ 29 ]. It is therefore possible that the administration of combination #4 also enhanced the hematopoietic function in the spleen instead of the damaged bone marrow of mice exposed to lethal TBI.…”
Section: Discussionmentioning
confidence: 99%